Islam and Democracy - Ahrar Ahmad (International Institute of Islamic Thought, 2003)
This paper challenges the popular perception that Islam and democracy are incompatible, and argues that the lack of democracy in some Muslim countries is not because of Islam but in spite of it. This argument will be developed in two stages. First, it will consider the legal–ethical order embedded in Islam’s text (the Qur’an) and tradition (prophetic example) to consider the democratic implications inherent in that construction. Second, it will explore three “high periods” of Islamic rule to consider their progressive, inclusive, and democratic tendencies. It will suggest that the current problems of democracy experienced by many Muslim countries are not necessarily caused by factors intrinsic to Islam, but by forces external to those areas.